HUBUNGAN PET ATTACHMENT DENGAN KESEPIAN PADA MAHASISWA RANTAU YANG BERTEMPAT TINGGAL DI KOS - Geraldine, Zettira; Uningowati, Dwi Wahyuni (FAKULTAS EKONOMI DAN PSIKOLOGI UNWIDHA KLATEN, 2023)
This research aims to determine the relationship between pet attachment and loneliness in overseas students who live in boarding houses. Respondents who took part in this study were overseas students who had pets in boarding houses in total 127 subjects. The scale used to test pet attachment is the Lexinton Attachment to Pet Scale developed by Johnson et al. (1992) adapted by Maranatha (2017), while the scale for measuring loneliness is the UCLA Loneliness Scale Ver.3 developed by Russel (1996) adapted by Pramitha (2018). The results of the analysis that has been carried out show that there is a negative relationship between pet attachment and loneliness. This proves that the higher the individual's perceived pet attachment, the lower the feeling of loneliness